Sustaining Fixed Rates: The Political Economy of Currency Pegs in Latin America - S. Brock Blomberg; Jeffry Frieden; Ernesto Stein (Wellesley College, Department of Economics, 2001)
This paper studies Latin American exchange rate regimes since 1960. We model government exchange rate regime choice, constrained by politics. The model implies that the larger the tradable sectors exposed to international competition, the less likely is the maintenance of a fixed exchange rate regime. It also implies that the probability of the maintenance of a fixed exchange rate increases as an election approaches. We evaluate these implications with hazard models to analyze the duration dependence of Latin American exchange rate arrangements from 1960 to 1994. We find substantial empirical evidence to support the model. Results are robust to the inclusion of a variety of other economic and political variables, to different time and country samples, and to different definitions of regime arrangement. Controlling for economic factors, a one percentage point increase in the size of the manufacturing sector is associated with a reduction of six months in the longevity of a country?s currency peg. An impending election increases the conditional likelihood of staying on a peg by about 8 percent, while the aftershock of an election conversely increases the conditional probability of going off a peg by 4 percent.
Keywords: 330; Wechselkurspolitik; Fester Wechselkurs; Lateinamerika